2015
DOI: 10.1093/brain/awv212
|View full text |Cite|
|
Sign up to set email alerts
|

A new knock-in mouse model of l-DOPA-responsive dystonia

Abstract: Abnormal dopamine neurotransmission is associated with many different genetic and acquired dystonic disorders. For instance, mutations in genes critical for the synthesis of dopamine, including GCH1 and TH cause l-DOPA-responsive dystonia. Despite evidence that implicates abnormal dopamine neurotransmission in dystonia, the precise nature of the pre- and postsynaptic defects that result in dystonia are not known. To better understand these defects, we generated a knock-in mouse model of l-DOPA-responsive dysto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 73 publications
6
59
0
Order By: Relevance
“…For example, the basal ganglia and dopamine neurotransmission are associated with many dystonic disorders, such as L-DOPA-responsive dystonia, which is caused by defects in enzymes necessary for the synthesis of catecholamines and ameliorated by L-DOPA treatment. In a knock-in mouse model of L-DOPA-responsive dystonia, restoration of catecholamine synthesis in the striatum via striatal L-DOPA administration ameliorates the dystonic movements, but administration of L-DOPA directly to the cerebellum is ineffective [54], demonstrating that the cerebellum is not always central to or even involved in the expression of dystonia. Thus, the many forms and etiologies of dystonia likely reflect the diversity of brain regions and biochemical defects underlying this heterogeneous disorder.…”
Section: How Does the Cerebellum Fit Into The Functional Neuroanatomymentioning
confidence: 99%
“…For example, the basal ganglia and dopamine neurotransmission are associated with many dystonic disorders, such as L-DOPA-responsive dystonia, which is caused by defects in enzymes necessary for the synthesis of catecholamines and ameliorated by L-DOPA treatment. In a knock-in mouse model of L-DOPA-responsive dystonia, restoration of catecholamine synthesis in the striatum via striatal L-DOPA administration ameliorates the dystonic movements, but administration of L-DOPA directly to the cerebellum is ineffective [54], demonstrating that the cerebellum is not always central to or even involved in the expression of dystonia. Thus, the many forms and etiologies of dystonia likely reflect the diversity of brain regions and biochemical defects underlying this heterogeneous disorder.…”
Section: How Does the Cerebellum Fit Into The Functional Neuroanatomymentioning
confidence: 99%
“…Mutations in TH are associated with neurological disorder of TH deficiency (THD)22, with phenotype ranging from mild L-DOPA responsive dystonia (type A)23 to a progressive encephalopathy with L-DOPA-unresponsive parkinsonism (type B)24. Furthermore, it has also been suggested that TH plays a pathogenic role in PD, either through generation of reactive oxygen species (ROS) during catalysis, especially by uncoupled reactions, and/or as a consequence of enzyme dysregulation252627.…”
mentioning
confidence: 99%
“…As in some other recessive disorders, we hypothesize that heterozygosity in TH-DRD could lead to a benign form of a typically severe disease, possibly due to a mild reduction in TH activity. Supporting this hypothesis, a small but significant reduction in striatal levodopa was observed in the post-mortem brain tissue of a heterozygous knock-in mouse model replicating a human TH mutation, as opposed to the profound reduction seen in the homozygous mouse model, demonstrating that the effect may be dependent on gene dosage [6]. Further studies of adult-onset DRD cases without GCH1 mutations may identify similar cases and provide further insights into the genetic spectrum of this condition.…”
Section: Manuscriptmentioning
confidence: 80%